Where greenspace matters most: A systematic review of urbanicity, greenspace, and physical health - Browning, Matthew H.E.M.; Rigolon, Alessandro; McAnirlin, Olivia; Yoon, Hyunseo (Violet) (Landscape and urban planning, 2022)
•We reviewed 37 articles on how urbanicity modifies the greenspace-physical health relationship.•Most articles showed greenspace promoted health equally well across urban–rural gradients.•However, an urban advantage was found for cardiovascular, birth, and mortality outcomes.•An urban advantage was also found for greenspace measured closer to home (e.g., smaller buffer radii).•Findings may relate to the mechanistic pathways in nature–health relationships. Greenspace in urban areas may have greater protective health effects than elsewhere. Urban dwellers experience more environmental harmful exposures, attentional demands, and stressors than their suburban/rural counterparts. In this systematic review, we synthesize the results of studies that examined how the greenspace and health relationship varies by urbanicity. We searched for articles in April 2019 that found positive associations between greenspace and physical health. Included articles tested for effect modification by urbanicity among one or more (of eight total) outcomes relevant to health and environmental equity. We coded results as 1 = stronger association in more urban areas, −1 = stronger association in less urban areas, or 0 = no difference. We found 57 analyses in 37 articles that met our inclusion criteria. Among these analyses, 50.9% showed no difference, 38.6% showed a stronger association for more urban areas, and 10.5% showed a stronger association for less urban areas. More urban areas had stronger associations for cardiovascular-related, birth, and mortality outcomes and for greenspace measured within 500 m. Stronger greenspace-health associations in more urban areas might be explained in part by the mechanistic pathways underlying these associations. Greenspace can reduce harms from environmental exposures (i.e., air pollution, noise, heat, and artificial light at night) in addition to alleviating attentional demands, reducing chronic stressors, and promoting healthy behavior - factors which might be more necessary, prevalent, or stronger in urban areas. These potential explanations warrant further investigation. The findings of this review inform public health policy and planning professionals who are attempting to make cities livable for all residents.